Heating processes in solidification of blooms - Yu. S. Postolnik; V. I. Timoshpolski; I. A. Trusova; O. V. Dubina (Литьë и металлургия)
The article gives analytical solution to the ingot solidification problem based on the “equivalent sources method”. Accuracy and correctness of the obtained final relations are proved.